Does Extending Unemployment Benefits Improve Job Quality? - Arash Nekoei; Andrea Weber (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2014)
Contrary to standard search model predictions, prior studies failed to estimate a positive effect of unemployment insurance (UI) on reemployment wages. This paper estimates a positive UI wage effect exploiting an age-based regression discontinuity in Austrian administrative data. A search model incorporating duration dependence determines the UI wage effect as the balance between two offsetting forces: UI causes agents to seek higher-wage jobs, but also reduces wages by lengthening unemployment. This implies a negative relationship between the UI unemployment-duration and wage effects, which holds empirically both in our sample and across studies, reconciling disparate wage-effect estimates. Empirically, UI raises wages by improving reemployment firms' quality and attenuating wage drops.
Keywords: 330